2009
DOI: 10.1097/fpc.0b013e32831d0faf
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*3505 allele is a strong predictor for nevirapine-induced skin adverse drug reactions in HIV-infected Thai patients

Abstract: A strong association between the HLA-B*3505 and NVP-induced skin rash provides a novel insight into the pathogenesis of drug-induced rash in the HIV-infected population. On account of its high specificity (98.9%) in identifying NVP-induced rash, it is possible to utilize the HLA-B*3505 as a marker to avoid a subset of NVP-induced rash, at least in Thai population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 171 publications
(147 citation statements)
references
References 28 publications
5
138
1
3
Order By: Relevance
“…The simultaneous presence of allele HLA-DRB1*01:01 and a CD4+ T lymphocyte count greater than 25% significantly increases the risk for hypersensitivity and hepatotoxicity reactions to NVP [24,25]. Similar associations have also been established for others HLA class I alleles such as HLA*B14:02, HLA-Cw08 and HLA-B*35:05 [26][27][28].…”
Section: Cyp2b6-g516gg (Common Genotype)supporting
confidence: 53%
“…The simultaneous presence of allele HLA-DRB1*01:01 and a CD4+ T lymphocyte count greater than 25% significantly increases the risk for hypersensitivity and hepatotoxicity reactions to NVP [24,25]. Similar associations have also been established for others HLA class I alleles such as HLA*B14:02, HLA-Cw08 and HLA-B*35:05 [26][27][28].…”
Section: Cyp2b6-g516gg (Common Genotype)supporting
confidence: 53%
“…Study population: This is a retrospective case-control study conducted on 85 HIV-infected patients who visited the Infectious Diseases Clinic of Ramathibodi Hospital, Mahidol University, in Bangkok, Thailand between March 2006 and February 2007; these patients were from a previous study (7,(19)(20)(21). The inclusion criteria were as follows: the HIV-infected patients should be adults (15 years old) who were maintained on antiretroviral regimens.…”
Section: Methodsmentioning
confidence: 99%
“…DNA isolation: Genomic DNA was isolated using a standard phenol-chloroform extraction protocol, resuspended in Tris-HCL buffer (pH 8.5) (19), and quantitated using UV spectrophotometer ND-1000 (Nano Drop Technologies, Rockland, DE, USA). The quality of the isolated DNA was determined by calculating the ratio of the absorbance at 260 and 280 nm (A 260/280 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently it was found that HLA B*3505 allele 17 as a strong predictor for nevirapine induced skin reactions in HIV infected patients. So,cost effective methods should be developed to diagnose HLA B*3505 allele to prevent drug reactions.…”
Section: Conclusion:-mentioning
confidence: 99%